ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Dede Prasetyo; Rikha Muftia Khoirunnisa (Universitas Ahmad Dahlan, 2015)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Current Ratio (CR) and Net Profit Margin (NPM) to share prices. the statistical method used is a model multiple linear regression. The sample in this study was a pharmaceutical company. The results showed that together (simultaneously) variables Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Current Ratio (CR) and Net Profit Margin (NPM) significantly influence stock prices. While partially, Debt to Equity Ratio (DER) with significance, Current Ratio (CR) is proven to have a significant effect on stock prices. Whereas that has no effect on price is Total Asset Turnover (TATO) and Net Profit Margin (NPM).